Hypercrosslinked functionalized lignosulfonates prepared via Friedel–Crafts alkylation reaction for enhancing Pb(Ⅱ) removal from aqueous. Issue 17 (22nd November 2019) - Zhu, Dailian; Qin, Cunqi; Ao, Shanshi; Wang, Mei; Wu, Minghua; lü, Yaohong; Pei, Kemei; Ni, Huagang; Ye, Peng
ABSTRACT: Hypercrosslinked functionalized lignosulfonates (CLS) were prepared by Friedel–Crafts alkylation reaction. The structure of CLS without introducing any functional groups and the according adsorption behaviors of Pb(II) were characterized and studied, respectively. Due to increase of specific surface area and abundance exposure of binding sites, the maximum adsorption capacity of CLS was found to be as high as 74.45 mg/g, which was about seven times that of raw lignin. The results provide a new feasible synthesis method for preparing lignin-based materials with porous structures and promising application for the removal of heavy metal ions from wastewater.